2018
DOI: 10.2196/10314
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Evidence-Informed Physical Activity Apps: Content Analysis

Abstract: BackgroundRegular moderate to vigorous physical activity is essential for maintaining health and preventing the onset of chronic diseases. Both global rates of smartphone ownership and the market for physical activity and fitness apps have grown rapidly in recent years. The use of physical activity and fitness apps may assist the general population in reaching evidence-based physical activity recommendations. However, it remains unclear whether there are evidence-informed physical activity apps and whether beh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
5
7
0
2
Order By: Relevance
“…Despite guidance for the development and evaluation of mobile apps [ 25 , 40 ], the quality ratings of the apps included in our review were mixed. This finding is consistent with reviews of publicly available rheumatology self-management apps [ 20 - 22 ] and apps targeting PA and exercise in the general population [ 41 , 42 ]. For example, Simoes et al [ 43 ] identified 51 moderate-quality PA apps for use by the general population (MARS total score 3.16 to 4.41) with the functionality and esthetics domains scoring most highly.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Despite guidance for the development and evaluation of mobile apps [ 25 , 40 ], the quality ratings of the apps included in our review were mixed. This finding is consistent with reviews of publicly available rheumatology self-management apps [ 20 - 22 ] and apps targeting PA and exercise in the general population [ 41 , 42 ]. For example, Simoes et al [ 43 ] identified 51 moderate-quality PA apps for use by the general population (MARS total score 3.16 to 4.41) with the functionality and esthetics domains scoring most highly.…”
Section: Discussionsupporting
confidence: 88%
“…The other apps did not completely align with PA recommendations, similar to other research [ 41 , 42 ]. Common reasons for apps not completely adhering to the PA guidance were the lack of or incorrect specific PA dosages (eg, sets, repetitions).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Good developmental practices would involve all stakeholders (clinicians and the target audience) as well as using evidence-based guidance from the beginning and at all stages of development and testing. The absence of the use of guidance or standards has recently been noticed for physical activity and fitness apps where very few of the thousands of Android apps provided any measurement or used any of the accepted guidance [50]. We especially emphasize including the target audience.…”
Section: Transparency For Trust (T4t) Principlesmentioning
confidence: 99%
“…Along with the booming of smartphone ownership, there is an increase consumer interest in measuring physical activity (PA) which helps individuals in recording their daily activities through applications [20]. The benefits on Android smartphones in health aspect such as MyMedSchedule,…”
Section: Introductionmentioning
confidence: 99%